The Explanation of Adolescent Delinquent Behaviors Based on Jessor's Problem Behavior Theory (PBT) in Iran: The Role of Individual Vulnerability, Opportunity Risk Availability, and Perceived Support - Darvishi, Mona; Atef Vahid, Mohammad Kazem; Elhami Athar, Mojtaba; Trejos-Castillo, Elizabeth; Habibi Asgarabad, Mojtaba (Frontiers in Psychiatry, 2022)
This study tested the generality of Problem Behavior Theory (PBT) in explaining adolescents' problem behavior in Iran. Data were collected from 392 adolescents (Mage = 15.97, SD = 1.12, 55.4% girls) who completed the Adolescent Health and Development Questionnaire (AHDQ) to assess the individual vulnerability, opportunity risk availability, perceived support, and delinquent behaviors. Results indicated that individual vulnerability and opportunity risk availability had a significant relationship with delinquent behaviors and a significant interaction with perceived support in their influence on delinquent behaviors. Further, perceived support was negatively associated with delinquent behaviors. Our results were consistent with PBT's explanatory model for adolescents' problem behavior in Western countries and are informative about problem behavior involvement among Iranian adolescents and the design of interventions.